Characterization of prostatic cancer lesion and gleason grade using a continuous-time random-walk diffusion model at high b-values - Sheng, Yurui; Chang, Huan; Xue, Ke; Chen, Jinming; Jiao, Tianyu; Cui, Dongqing; Wang, Hao; Zhang, Guanghui; Yang, Yuxin; Zeng, Qingshi (Frontiers in Oncology, 2024)
Background: Distinguishing between prostatic cancer (PCa) and chronic prostatitis (CP) is sometimes challenging, and Gleason grading is strongly associated with prognosis in PCa. The continuous-time random-walk diffusion (CTRW) model has shown potential in distinguishing between PCa and CP as well as predicting Gleason grading. Purpose: This study aimed to quantify the CTRW parameters (α, β & Dm) and apparent diffusion coefficient (ADC) of PCa and CP tissues; and then assess the diagnostic value of CTRW and ADC parameters in differentiating CP from PCa and low-grade PCa from highgrade PCa lesions. Study type: Retrospective(retrospective analysis using prospective designed data). Population: Thirty-one PCa patients undergoing prostatectomy (mean age 74 years, range 64-91 years), and thirty CP patients undergoing prostate needle biopsies (mean age 68 years, range 46-79 years).